PERAN GURU DALAM IMPLEMENTASI SIKAP TANGGUNG JAWAB MELALUI TRI NGA (NGERTI, NGRASA, NGLAKONI) SISWA KELAS V SD N 1 MUTIHAN - Dewi Kunti Setiyowati; Trisharsiwi Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
This study aims to describe the role of teachers to overcome the problem of implementing an attitude of responsibility through the teaching of Tri Nga (ngerti, ngrasa, nglakoni) in grade V students of SD N 1 Mutihan. The research was conducted at SD N 1 Mutihan, November-January 2022. The subject of the study, the principal, the teacher of class V, and the students of class V. Data collection techniques: observation, interview, documentation. Research instruments: observation guidelines, interview guidelines, documentation guidelines. Test the validity of the data: triangulation of engineering sources, time, using reference materials. Data analysis techniques using Miles Huberman data analysis: data collection, data reduction, data presentation, conclusion drawing. The results showed that the role of teachers in the implementation of responsibilities, teachers play the role of educators, models, examples, mentors, directors, advisors, provide direction if students are wrong, give good examples, and teach students to have good responsibilities. Supporting factors are the availability of school facilities, the cooperation of school residents, the attitude of teachers, and positive habituation. inhibiting factors, the student's self, family background, socio-culture, and surrounding environment. Efforts to overcome these problems, understand the importance of responsibility, encourage, and motivate, communicate with parents, and share with teachers.